NÅR STEDER OPLØSES: Russeres begrebsliggørelse af et Riga under forandring - Rosengaard, Camilla (Tidsskriftet Antropologi, 1997)
Camilla Rosengaard: When Places Disintegrate This paper focuses on how ethnic Russians attempt to oppose the processes of deterritorialization they are subject to in the newly established Latvian State. The attempt on behalf of the Latvian State to marginalise the Russians is - among other things - expressed in the spatial restructuration of Latvia’s Capital Riga. Markers and signs refering to the Russian community and the Soviet past to a large extern are removed from the city-scape. In keeping a tour-map of all the removed places in mind, the Russians manage to keep track on the Soviet place and thereby create a continuity with the past. In creating this discursive place, the Russians challenge the official Latvian history and their role in it as foreigners who are not granted citizenship.